THE PROBLEM OF NORMATIVITY IN EXPLANATORY ENGLISH DICTIONARIES - Mudgal, Abhay Mudgal (Galaxy International Interdisciplinary Research Journal, 2023)
An academic type dictionary is a normative one that describes the lexical system of a given language: it should not contain facts that contradict modern usage. The article is devoted to the issues of normativity in explanatory English dictionaries such as there is given a great number of examples along with plausible justification to the work.